Inference of Soil Hydrologic Parameters from Electronic Soil Moisture Records - Chandler, David G.; Seyfried, Mark S.; McNamara, James P.; Hwang, Kyotaek (Frontiers in Earth Science, 2017)
Key Points Soil hydrologic parameters including field saturation, field capacity, initiation of plant water stress and plant extraction limits can be reliably determined from electronic soil moisture sensor records. Soil profile wetting and drying occurs along a regular continuum of soil moisture following the advance of the wetting from to the effective base of the soil profile. Frozen soil conditions and interactions between energy and water limited water balances complicate interpretations of fluxes in the soil-plant-atmosphere continuum. Soil moisture is an important control on hydrologic function, as it governs vertical fluxes from and to the atmosphere, groundwater recharge, and lateral fluxes through the soil. Historically, the traditional model parameters of saturation, field capacity, and permanent wilting point have been determined by laboratory methods. This approach is challenged by issues of scale, boundary conditions, and soil disturbance. We develop and compare four methods to determine values of field saturation, field capacity, plant extraction limit (PEL), and initiation of plant water stress from long term in-situ monitoring records of TDR-measured volumetric water content (Θ). The monitoring sites represent a range of soil textures, soil depths, effective precipitation and plant cover types in a semi-arid climate. The Θ records exhibit attractors (high frequency values) that correspond to field capacity and the PEL at both annual and longer time scales, but the field saturation values vary by year depending on seasonal wetness in the semi-arid setting. The analysis for five sites in two watersheds is supported by comparison to values determined by a common pedotransfer function and measured soil characteristic curves. Frozen soil is identified as a complicating factor for the analysis and users are cautioned to filter data by temperature, especially for near surface soils.